Temporal and Spatial Evolution of Laser-Induced Plasma from a Slag Sample - 王静鸽 付洪波 倪志波 陈兴龙 贺文干 董凤忠 (Plasma science & technology, 2015)
Laser-Induced Breakdown Spectroscopy （LIBS） has been demonstrated to be an effective method for slag analysis. In order to better clarify the nature of the plasma generated from a slag sample, an Nd：YAG pulse laser at 1064 nm wavelength was used to ablate the slag sample in air. The temporal and spatial evolutions of plasma parameters, including emission intensity, electronic density and plasma temperature, have been studied. It is shown that the electron density and plasma temperature drop off rapidly with the delay time as a result of plasma expansion and cooling. It has been found that the electron density of the whole plasma is close to that of the center regions in the plasma. The results of the spatial distributions on the two-dimensional plane have shown that there is a big region with lower electron density values caused by the recombination process in the center of the plasma. The maximum of the plasma temperature takes place at the regions close to the target, and the border of the plasma front-head has higher plasma temperatures than that of the center part.